Adsorption of SARS‐CoV‐2 Spike Protein S1 at Oxide Surfaces Studied by High‐Speed Atomic Force Microscopy. Issue 2 (18th December 2020) - Xin, Yang; Grundmeier, Guido; Keller, Adrian
Abstract : The ongoing coronavirus disease 2019 (COVID‐19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) represents a serious threat to the health of millions of people. Respiratory viruses such as SARS‐CoV‐2 can be transmitted via airborne and fomite routes. The latter requires virion adsorption at abiotic surfaces and most likely involves the SARS‐CoV‐2 spike protein subunit 1 (S1), which is the outermost point of its envelope. Understanding S1 spike protein interaction with fomite surfaces thus represents an important milestone on the road to fighting the spread of COVID‐19. Herein, high‐speed atomic force microscopy (HS‐AFM) is used to monitor the adsorption of the SARS‐CoV‐2 spike protein S1 at Al2 O3 (0001) and TiO2 (100) surfaces in situ. While the single‐crystalline oxide substrates are chosen to model the native surface oxides of Al‐ and Ti‐based fomites, adsorption is studied in electrolytes that mimic the pH and major ionic components of mucosal secretions and saliva, respectively. Quantitative analysis of the obtained HS‐AFM images indicates that S1 spike protein adsorption at these surfaces is mostly governed by electrostatic interactions with possible contributions from van der Waals interactions. It thus proceeds more rapidly at the TiO2 (100) than at the Al2 O3 (0001) surface. Abstract : The adsorption of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) spike protein subunit 1 (S1) at Al2 O3 and TiO2 surfaces is investigated under electrolyte conditions mimicking different bodily fluids by high‐speed atomic force microscopy. Quantitative image analysis reveals that S1 protein adsorption at these two fomite surfaces is driven by electrostatic interactions with possible contributions of van der Waals interactions.